2000
DOI: 10.1021/bi000501x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by Ca2+ and by Membrane Binding of the Dynamics of Domain III of Annexin 2 (p36) and the Annexin 2−p11 Complex (p90):  Implications for Their Biochemical Properties

Abstract: The modulation of the local structure and dynamics of domain III of annexin 2 (Anx2), in both the monomeric (p36) and heterotetrameric forms (p90), by calcium and by membrane binding was studied by time-resolved fluorescence intensity and anisotropy measurements of the single tryptophan residue (W212). The results yield the same dominant excited-state lifetime (1.4 ns) in both p36 and p90, suggesting that the conformation and environment of W212 are very similar. The fluorescence anisotropy decay data were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
35
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 64 publications
7
35
2
Order By: Relevance
“…The cells were subsequently sonicated in lysis buffer (100 mM Tris-HCl, pH 7.5, 200 mM NaCl, 10 mM MgCl 2 , 2 mM dithiothreitol ϩ protease inhibitors) and centrifuged at 100,000 ϫ g for 1 h at 4°C. Both p11 mutants were purified in the same manner as wild-type p11 (23). Briefly, the cell lysis supernatant was precipitated with 50% (NH 4 ) 2 SO 4 , and the supernatant was applied to a butylSepharose column equilibrated in lysis buffer containing 50% (NH 4 ) 2 SO 4 .…”
Section: Purification Of Wild-type and Mutant P11-after 4 H Of Inductionmentioning
confidence: 99%
“…The cells were subsequently sonicated in lysis buffer (100 mM Tris-HCl, pH 7.5, 200 mM NaCl, 10 mM MgCl 2 , 2 mM dithiothreitol ϩ protease inhibitors) and centrifuged at 100,000 ϫ g for 1 h at 4°C. Both p11 mutants were purified in the same manner as wild-type p11 (23). Briefly, the cell lysis supernatant was precipitated with 50% (NH 4 ) 2 SO 4 , and the supernatant was applied to a butylSepharose column equilibrated in lysis buffer containing 50% (NH 4 ) 2 SO 4 .…”
Section: Purification Of Wild-type and Mutant P11-after 4 H Of Inductionmentioning
confidence: 99%
“…In the case of AnxA5, it results in the swinging out of Trp-187 in repeat III from a buried to a solvent-exposed position (10 -14). Trp-212 in AnxA2 detects also a Ca 2ϩ -induced conformational change in repeat III, but this residue remains buried in the protein (15,16). The major difference between the membrane-free and the membrane-bound forms of annexin 2 is the Ca 2ϩ sensitivity.…”
mentioning
confidence: 99%
“…Others, including AnxA1 and AnxA2 form membrane junctions with or without protein ligands attached to their N-terminal segment (7)(8)(9)(10)(11). The classical mechanism described for these two processes involves a primary Ca 2ϩ -dependent membrane binding step leading to conformational changes of the core domain, in particular of repeat III (12)(13)(14)(15)(16)(17)(18). The N-terminal domain of Anxs also plays an important role in the specific membrane aggregative properties.…”
mentioning
confidence: 99%
“…The N-terminal domain of Anxs also plays an important role in the specific membrane aggregative properties. In particular, the N-terminal domain of AnxA1 and AnxA2 interacts strongly with proteins of the S100 family, resulting in a severalfold increase in the Ca 2ϩ sensitivity of membrane aggregation (17). Recently, we showed that the N-terminal domain of monomeric AnxA2 was also involved in the Ca 2ϩ -dependent membrane bridging at neutral pH: we demonstrated interactions between the N-terminal domains of two adjacent AnxA2 molecules, which were not in direct contact with the membrane phospholipids (19).…”
mentioning
confidence: 99%